Mini-Review: Human Microbiome and Rheumatic Diseases - Vural, Meltem; Gilbert, Benoit; Üstün, Işıl; Caglar, Sibel; Finckh, Axel (Frontiers in Cellular and Infection Microbiology, 2020)
Rheumatoid arthritis and spondyloarthropathy are the most common inflammatory rheumatic diseases. As the human microbiome is involved in the immune homeostasis, it has the potential to be a key factor in the development of autoimmune diseases and rheumatic diseases. In this article, we review the role of various human microbiota on the pathogenesis of rheumatic diseases, focusing on spondylarthritis and rheumatoid arthritis.